Value Addition to Human Managerial Skills in the Livestock Sector in Nigeria - A. A, Adeyemo; M. P, Longe; A. A, Alakoso (Asian Journal of Agriculture and Rural Development, 2014)
Value addition is an important concept in Nigeria’s agriculture, including the livestock sub-sector. Its definition is often given with special emphasis on and with respect to agricultural products. However, the general principle in value addition is the process of transforming resources, including human, from its original state to a more valuable state. In the livestock industry, human is a critical resource and adding value to its status should be the arrow head of developing the sub-sector. Most people in the sub-sector are academically sound and technically competent in their respective fields of specialisation but gaps exist in their management skills and acumen. There is the need for value addition to the human managerial skills of Officers managing livestock activities in the country. Governments at all levels should endeavour to provide financial and institutional supports towards the achievement of this goal. This will provide impetus on fully actualising the robust agricultural transformation agenda of the country.